Making European space : mobility, power and territorial identity - Jensen, Ole B. (Ole Brandt); Richardson, Tim (Writer on city planning) (Routledge, 2004)
Making European Space crystallises and critically examines the key policy ideas emerging in the new field of European spatial planning, and explores the arguments surrounding policy themes such as polycentric development, sustainability.